'I wouldn't choose this work again': Perspectives and experiences of care aides in long‐term residential care. (7th July 2021) - Booi, Laura; Sixsmith, Judith; Chaudhury, Habib; O'Connor, Deborah; Young, Melanie; Sixsmith, Andrew
Abstract: Aims: To provide insight into the everyday realities facing care aides working in long‐term residential care (LTRC), and how they perceive their role in society. Design: A qualitative ethnographic case study. Methods: Data were collected over. 10 months of fieldwork at one LTRC setting [September 2015 to June 2016] in Western Canada; semi‐structured interviews (70 h) with 31 care aides; and naturalistic observation (170 h). Data were analysed using reflexive thematic analysis. Results: The findings in this work highlight the underpinned ageism of society, the gendered work of body care, and the tension between the need for relational connections – which requires time and economic profit. Four themes were identified, each relating to the lack of training, support, and appreciation care aides felt about their role in LTRC. Conclusion: Care aides remain an unsupported workforce that is essential to the provision of high‐quality care in LTRC. To support the care aide role, suggestions include: (i) regulate and improve care aide training; (ii) strengthen care aides autonomy of their care delivery; and (iii) reduce stigma by increasing awareness of the care aide role. Impact: What problem did the study address? The unsupportive working conditions care aides experience in LTRC and the subsequent poor quality of care often seen delivered in LTRC settings. What were the main findings? Although care aides express strong affection for the residents they care for, they experience insurmountable systemic and institutional barriers preventing them from delivering care. Where and on whom will the research have impact? Care aides, care aide educators, care aide supervisors and managers in LTRC, retirement communities, and home care settings.